Religious Traditions and Health Care Policy: Potential for Democratic Discourse? - Cochran, Clarke E. (A journal of church and state, 1997)
Clarke E. Cochran; Religious Traditions and Health Care Policy: Potential for Democratic Discourse?, Journal of Church and State, Volume 39, Issue 1, 1 January